2011
DOI: 10.1177/0022034511407335
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Trioxide Aggregate Inhibits Osteoclastic Bone Resorption

Abstract: Mineral trioxide aggregate (MTA), a commonly used endodontic repair material, is useful for both basic and clinical research, and the effect of MTA on osteoblast differentiation has been well-defined. However, the effects of MTA on osteoclastic bone resorption are not fully understood. Hence, the aim of this study is to examine the effect of MTA solution in the regulation of osteoclast bone-resorbing activity using osteoclasts formed in co-cultures of primary osteoblasts and bone marrow cells. MTA solution dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
(34 reference statements)
0
21
0
2
Order By: Relevance
“…Ample reports are available that examined the effects of Ca- and Si-containing biomaterials in promoting or suppressing the differentiation of osteoblast or osteoclast precursors. These materials include Si-substituted apatite [28,29], bioactive glasses [12,30] and calcium silicate cements [31,32]. While all of these materials were found to stimulate differentiation of osteoblast precursors and bone formation, their effects on osteoclastogenesis and cell-mediated bone degradation were ambiguous and appeared to be material-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Ample reports are available that examined the effects of Ca- and Si-containing biomaterials in promoting or suppressing the differentiation of osteoblast or osteoclast precursors. These materials include Si-substituted apatite [28,29], bioactive glasses [12,30] and calcium silicate cements [31,32]. While all of these materials were found to stimulate differentiation of osteoblast precursors and bone formation, their effects on osteoclastogenesis and cell-mediated bone degradation were ambiguous and appeared to be material-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…TRAP-positive multinuclear cells [TRAP(ϩ)], containing more than three nuclei, were regarded as osteoclasts. Bone resorption assay using a dentine slice and F-actin ring staining were performed according to the method described (31).…”
Section: Methodsmentioning
confidence: 99%
“…Hashiguchi et al (2011) investigated that MTA inhibits bone resorption. Taken together, we concluded that MTA in endodontic treatment may affect alveolar bone healing in the resorbed region caused by pulpal infection.…”
Section: Discussionmentioning
confidence: 99%